EXTH-49. NOVEL AD-REIC VECTOR WITH THE SUPER GENE EXPRESSION (SGE) SYSTEM (AD-SGE-REIC) AS A PROMISING THERAPEUTIC AGENT FOR MALIGNANT GLIOMA. (5th November 2018) - Kurozumi, Kazuhiko; Oka, Tetsuo; Fujii, Kentaro; Hattori, Yasuhiko; Tomita, Yusuke; Shimizu, Toshihiko; Uneda, Atsuhito; Matsumoto, Yuji; Kumon, Hiromi; Date, Isao
Abstract: INTRODUCTION: Reduced expression in immortalized cells/Dickkopf-3 (REIC/Dkk-3) is a tumor suppressor and therapeutic gene in many human cancers. We have investigated the anti-glioma effect of the adenovirus vector carrying REIC/Dkk-3 (Ad-CAG-REIC). Recently an Ad-REIC vector with the super gene expression (SGE) system (Ad-SGE-REIC) has been developed for higher protein expression and therapeutic effects than the conventional adenoviral vector (Ad-CAG-REIC). In this study, we evaluated the anti-glioma effect of the Ad-SGE-REIC against malignant glioma. MATERIALS AND METHODS: Transcriptome analysis of the differential (exome sequencing-derived) expression levels of REIC was conducted based on using The Cancer Genome Atlas (TCGA) GBM patient dataset (n=349) using the Project Betastasis web platform (http://www.betastasis.com/glioma/tcga_gbm/ ). To evaluate the anti-glioma effect of the Ad-SGE-REIC, we conducted a cytotoxicity assay to assess treatments with Ad-SGE-REIC, Ad-CAG-REIC, or Ad-LacZ (control) using malignant glioma cells (U87ΔEGFR or GL261) and normal human astrocytes (NHAs). Seven days after implantation of glioma cells into the brain of mice, Ad-SGE-REIC, Ad-CAG-REIC, or Ad-LacZ (control) was injected stereotactically at the tumor inoculation site. The survival of mice in each group was analyzed by the Kaplan–Meier method. RESULTS: Analysis of the TCGA GBM patient dataset revealed that differential expression levels of REIC were lower in all subgroups, including Proneural, Neural, Classical, and Mesenchymal groups, than in the control group. In the cytotoxicity assay, after treatment with Ad-SGE-REIC, the number of malignant glioma cells attached to the bottom of culture wells was significantly reduced in a time-dependent manner. The survival time of the mice treated with Ad-SGE-REIC was significantly longer than those treated with Ad-LacZ or Ad-CAG-REIC. CONCLUSIONS: We demonstrated the anti-glioma effect of Ad-SGE-REIC. We are now planning an investigator-initiated clinical trial (phase I/IIa) of Ad-SGE-REIC for the treatment of recurrent malignant glioma.